Cellulose, cellulose/polysaccharide or cellulose/protein blend materials prepared from a novel solvent system for use in medical applications - Douglass, E. F.; Kotek, R. (Nazarbayev University, 2013)
A new environmentally friendly solvent system has been developed to make cellulose and cellulose blend membranes. It was determined there was a need to see if this novel system could be used for membrane production, we were successful. These membranes were produced, and they were characterized, and found to have physical properties comparable with current cellulose membranes. We then used these results to attempt the development of blend materials, with unique properties. We developed these membranes with pure cellulose and blended with another natural biomaterial to make a composite membrane with unique properties. These compatible blends of starch or protein with cellulose had never been accomplished before. The methods of characterizing these materials are also useful in determining compatibility of polymers with one another in a solid system. We discovered these new blend materials have interesting chemical and physical characteristics, and adding these biomaterials remains compatible at the macro and micro level with cellulose. These materials were then characterized and found to have physical properties similar to conventional cellulose membranes.
Keywords: first research week; medicine; cellulose membranes; hazardous waste production